ESG Part, Financial Distress, Financial Fraud and Audit Committee as a Moderating Variable - Imelda Imelda; Mukhtaruddin Mukhtaruddin; Kartasari F Shelly (International Journal Multidisciplinary Science, 2026)
This research is motivated by the increasing demands for transparency and accountability. Companies are not only required to present reliable financial reports but also to demonstrate their commitment to sustainability practices through ESG performance. On the other hand, financial distress can increase pressure on management to maintain company performance, potentially encouraging financial statement manipulation. The audit committee acts as an oversight mechanism that can improve the integrity of the financial reporting process. This study aims to analyze the effect of ESG performance and financial distress on financial statement fraud and to examine the moderating role of the audit committee in this relationship by considering differences in industry characteristics as a control variable. This study uses a quantitative approach with secondary data from 94 companies in the ASEAN region for the period 2017–2024 with a total of 752 observations. Data analysis was performed using panel data regression with the help of Eviews 14 software. The results show that ESG performance and financial distress have a significant effect on financial statement fraud. The results of the moderation test indicate that the audit committee is able to moderate the relationship between ESG and financial distress on financial statement fraud. Differences in industry sector characteristics can affect the level of ESG, the risk of financial distress, and the effectiveness of audit committee oversight in preventing financial statement fraud. These findings suggest that increasing corporate transparency depends not only on ESG but also on considering industry sector characteristics and adapting oversight strategies to minimize the potential for financial reporting fraud in the ASEAN region.